Structural modeling and calculation of thermal conductivity of polyimide composite materials - Borshchov, V.M.; Listratenko, O.M.; Protsenko, M.A.; Tymchuk, I.T.; Kravchenko, O.V.; Suddia, O.V.; Borshchov, I.V.; Slipchenko, M.I. (Radiotekhnika, 2022)
Issues of direct modeling effective thermal conductivity of two-component thermally conductive polyimide composite films based on polyimide thermosetting varnishes and thermally conductive powder fillers are considered. 3D-structural modeling of elementary cubic cells of polyimide composites has been performed. Calculations of average heat fluxes and effective thermal conductivity of variants of polyimide composite films with the introduction of highly thermally conductive highly dispersed and ultradispersed powder fillers into the polyimide matrix were carried out, including those from SiO2, SiC, Al2O3, AlN, taking into account boundary and initial conditions using COMSOL MULTIPHYSICS software. Specific recommendations are proposed for direct modeling of the thermal conductivity of environments with a complex structure and for carrying out with sufficient reliability numerical calculations of the effective thermal conductivity of polyimide composite films in order to increase their thermal conductivity from 0,12 W/(m•K) up to 1-4 W/(m•K) by changing concentration and thermal conductivity of mixtures of filler particles of micron and ultramicron sizes.